Fifth African Telecom Summit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A forum for deliberating on, and developing solutions to, critical ICT issues in Africa by Africans, in an African setting, with Africa´s business and investment partners.